Orientation - Gabriel Pulido (Journal Committed to Social Change on Race and Ethnicity)
This special issue of the Journal Committed to Social Change on Race and Ethnicity (JCSCORE) is introduced through a deeply personal and reflective orientation by guest editor Gabriel Pulido. Drawing from his journey with poetry as a first-generation U.S. citizen, Pulido positions poetry not only as an accessible and transformative art form but as a method of healing, resistance, and liberation. Anchored in the work of visionaries such as Audre Lorde, Gloria Anzaldúa, and Terisa Siagatonu, the introduction highlights poetry’s capacity to speak truth to power, foster community, and challenge capitalist values. Utilizing the six guiding principles—accessibility, capability, flexibility, reflexivity, temporality, and possibility—that shape the issue’s approach to poetry, Pulido invites readers to engage with the work not as observers but as co-dreamers. This issue uplifts poets who craft new modes of existence through their art and affirms poetry’s enduring role in collective healing and social transformation.